2008
DOI: 10.1029/2007jc004124
|View full text |Cite
|
Sign up to set email alerts
|

Pacific freshwater, river water and sea ice meltwater across Arctic Ocean basins: Results from the 2005 Beringia Expedition

Abstract: Pacific water, sea ice meltwater, and river water are the primary sources of freshwater in the Arctic Ocean. We have determined their relative fractions on a transect across the Arctic Ocean Section 2005 Expedition onboard IB Oden, which took place from 21 August to 23 September 2005. The transect began north of Alaska, continued through the central Canada Basin to the Alpha Ridge and into the Makarov Basin, and ended in Amundsen Basin. Pacific freshwater and river water were the major sources of freshwater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
137
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(151 citation statements)
references
References 42 publications
11
137
1
1
Order By: Relevance
“…3.2.5) may be due to formation processes on the Siberian shelves (Bauch et al, 2009(Bauch et al, , 2011a. Within the Transpolar Drift, Jones et al (2008a) observed IFB patches at depths below 50 m in the Eurasian Basin, vertically isolated from the much shallower summer surface mixed layer. Furthermore, summer observations in the shelf regions of the Laptev and Kara seas from 1999 to 2001 have shown that waters with salinities lower than 30 take different pathways from the shelf than those with higher salinities (Bauch et al, 2005).…”
Section: Changes In the Arctic Ocean Basinsmentioning
confidence: 97%
See 3 more Smart Citations
“…3.2.5) may be due to formation processes on the Siberian shelves (Bauch et al, 2009(Bauch et al, , 2011a. Within the Transpolar Drift, Jones et al (2008a) observed IFB patches at depths below 50 m in the Eurasian Basin, vertically isolated from the much shallower summer surface mixed layer. Furthermore, summer observations in the shelf regions of the Laptev and Kara seas from 1999 to 2001 have shown that waters with salinities lower than 30 take different pathways from the shelf than those with higher salinities (Bauch et al, 2005).…”
Section: Changes In the Arctic Ocean Basinsmentioning
confidence: 97%
“…1a and Dodd et al, 2012). This method uses a system of linear equations (endmember balance) to derive the aforementioned water mass fractions and fractions of Atlantic Water (AW) from each observed tracer, assuming certain end-member values for each tracer (see also Ekwurzel et al, 2001;Jones et al, 2008a;Yamamoto-Kawai et al, 2008). In addition to further years of observations, the main difference to previous work (Dodd et al, 2009;Rabe et al, 2009) is the inclusion of nitrate and phosphate observations to distinguish PW in the end-member balance.…”
Section: Velocity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exchange of dissolved O 2 with the atmosphere may lead to an underestimation of f p in the summer mixed layer (Bauch et al, 2011a). Bauch et al (2011a) thus additionally follow the procedure based on N/P presented by Jones et al (1998; and Yamamoto-Kawai et al (2008) using the "pure Pacific water" correlation line [NO x ] = 15.314· [PO 4 ] -14.395 (Jones et al, 2008) and an adjusted "pure Atlantic water" correlation line (Bauch et al, 2011a) [NO x ] = 16.785· [PO 4 ] -1.9126. On the other hand denitrification creates an apparent f p signal and Bauch et al (2011a) use the brine signal (negative fi) to identify this apparent f p within the Transpolar Drift.…”
Section: Balancing the Fresh Water Fraction In The Upper Water Columnmentioning
confidence: 99%